Increased rates of cetuximab reactions in tick prevalent regions and a proposed protocol for risk mitigation. Issue 6 (24th September 2020) - Yuile, Alexander; Fanuli, Claudia; van Nunen, Sheryl; Diakos, Connie; Clarke, Stephen; Steiner, Christian; MacMillan, Robyn; Oatley, Meredith; Pavlakis, Nick
Abstract: Background: Cetuximab is an anti‐epidermal growth factor receptor mouse‐human chimeric monoclonal antibody used to treat advanced colorectal cancers. Initial data suggest that severe infusion reactions occurred in 4.5%, many on first exposure. The majority of those with anaphylactic reactions possess predeveloped IgE antibodies to galactose‐alpha‐1, 3‐galactose. It is thought that the vector for preexposure to alpha‐gal is antigen inoculation via tick bites. This retrospective study reviews the experience of two community cancer centers in high tick exposure areas in Sydney with cetuximab anaphylaxis and proposes a protocol to avoid this. Method: Severe cetuximab infusion reactions occurring in the Northern Cancer Institute Frenchs Forest and St Leonards clinics, Sydney, from May 2014 to February 2019 were recorded. Area of residence was then compared to areas of known high tick prevalence. Results: A total of 87 patients received cetuximab in this period. Six patients (6.9%) experienced at least a grade 3 reaction, three females, age range 41–72 years (median 57.5 years). All were receiving cetuximab for metastatic colorectal cancer and their anaphylaxis occurred with the first infusion in all cases. Conclusion: These cases support the existing theory of increased rates of cetuximab anaphylaxis in areas of high tick prevalence. Given this, we recommend the following protocol for patients being considered for cetuximab therapy: known mammalian meat allergy as an absolute contraindication; all patients receiving cetuximab should have RAST (ImmunoCAP ® ) testing for alpha‐gal specific‐IgE‐specific antibodies before first infusion and those who test positive to be considered alternate therapy. Abstract : Rates of cetuximab anaphylaxis have been shown to be significantly higher in areas of high tick prevalence. This retrospective study reviews the experience of two community cancer centers in high tick exposure areas in Sydney with cetuximab anaphylaxis and proposes a protocol to avoid this.